Pentingnya Bepikir Filosofis dalam Proses Pendidikan - Lafinatu Asfiya; Shobrun jamil; Chaca Amaliya Tri Agustin; Kurnia Ahmad Susilo (Kayee: Jurnal Pendidikan dan Ilmu Sosial, 2026)
Education in the current era is facing various challenges, such as low critical thinking skills among students, the dominance of learning that tends to focus on academic grades, and the influence of technological developments and digital media that encourage instant mindsets. These conditions often cause the educational process to focus only on the transfer of knowledge without paying attention to the development of directed, logical, and meaningful ways of thinking. This article aims to examine the importance of philosophical thinking in the educational process as an effort to shape students who are critical, wise, and have character. The method used in this research is a literature study by reviewing various literature sources related to the philosophy of education and the problems of current-era education in Indonesia. The results of this study indicate that philosophical thinking plays a significant role in helping students understand the meaning of education, improving analytical and problem-solving skills, and building moral and social awareness. In addition, a philosophical approach can also create a more open, simple learning process, and oriented towards the development of human potential as a whole. Thus, the application of philosophical thinking in education is a crucial need to face the challenges of modern education in Indonesia.